Incidence and Predictors of Right Ventricular Reverse Remodeling in Patients with Transthyretin Amyloid Cardiomyopathy Treated with Tafamidis - Nicoleta Nita; Dominik Felbel; Michael Paukovitsch; Felix von Sanden; Elene Walter; Rima Melnic; Wolfgang Rottbauer; Dominik Buckert; Johannes Mörike (Biomedicines)
Background/Objectives: In patients with transthyretin amyloid cardiomyopathy (ATTR-CM), the effect of tafamidis on right ventricular (RV) dysfunction has been poorly investigated. The purpose of this study was to evaluate the effect of tafamidis on RV free wall global longitudinal strain (RV FW-GLS) and right ventricular and pulmonary artery (RV-PA) coupling over 12 months of treatment. Methods: Ninety-three patients with ATTR-CM treated with 61 mg of tafamidis daily who underwent multimodality imaging evaluation at baseline by cardiovascular magnetic resonance (CMR) and speckle-tracking echocardiography were retrospectively studied. The 12-month follow-up included an echocardiographic assessment of RV FW-GLS and RV-PA coupling. RV reverse remodeling was defined as a >10% improvement in RV FW-GLS and/or in RV-PA coupling from baseline. RV-PA coupling was assessed using the tricuspid annular plane systolic excursion/ pulmonary artery systolic pressure (TAPSE/PASP) ratio. Results: Over 12 months of tafamidis treatment, RV reverse remodeling was documented in 22.6% of patients. In these patients, RV FW-GLS improved significantly from 14.5 ± 2.1% to 17.3 ± 2%, p < 0.001, whereas the TAPSE/PASP ratio improved from 0.42 ± 0.05 mm/mmHg to 0.54 ± 0.07 mm/mmHg, p = 0.001. Patients who experienced RV reverse remodeling were at an earlier stage of disease prior to tafamidis treatment with less dilated RV and less severe RV-PA uncoupling (TAPSE/PASP ratio: 0.43 ± 0.06 mm/mmHg vs. 0.39 ± 0.06 mm/mmHg, p = 0.040). CMR-derived baseline RV end-systolic volume (HR 0.83, 95% CI 0.73–0.94, p = 0.005) and NT-proBNP (HR 0.989, 95% CI 0.988–0.999, p = 0.024) were the strongest independent predictors of RV reverse remodeling, followed by PASP (HR 0.82, 95% CI 0.69–0.98, p = 0.030). Conclusions: Patients with ATTR-CM treated with tafamidis at an earlier stage of the disease experienced RV reverse remodeling with significant improvement in RV FW-GLS and RV-PA coupling.